Enhancing Higher-Order Thinking Skills Through Multimedia-Based Inquiry Learning - Nugraha, Ketut Budi; Ade, Abdul (International Journal of Technology and Modeling, 2023)
The development of higher-order thinking skills (HOTS) is essential in science education to foster students’ critical, analytical, and problem-solving abilities. This study explores the effectiveness of multimedia-based inquiry learning in enhancing HOTS among middle school students in science subjects. By integrating multimedia elements—such as animations, simulations, and interactive modules—into an inquiry-based learning framework, students are encouraged to actively engage with scientific concepts through exploration, questioning, and evidence-based reasoning. A quasi-experimental design was employed, involving two groups: one experiencing traditional instruction and the other receiving multimedia-based inquiry learning. The results showed a significant improvement in HOTS among students in the experimental group, as measured by standardized HOTS assessments and classroom performance tasks. This study highlights the potential of multimedia-enhanced inquiry learning as a powerful pedagogical approach to promote deeper understanding and cognitive engagement in science education.